The logic of sense - Deleuze, Gilles (Continuum, 2004)
This is one of Deleuze's seminal works. Ranging from Stoic philosophy to Lewis Carroll's literary and logical paradoxes, Deleuze's exploration of meaning and meaninglessness takes in language games, sexuality, schizophrenia, psychoanalysis and literature.